Antihypertensive effects of Moringa oleifera leaf extract Lam. (Moringaceae) in NG-nitro-L-arginine-methyl ester-induced hypertensive rats - GBANKOTO, Adam; Sindete, Mariette; ADJAGBA, Marius; SANGAR, MAXIME MACHIOUD; ATTAKPA, S. EUGÈNE; AWEDE, BONAVENTURE L. SÉVERIN (My University, 2019)
The use of natural products such as Moringa oleifera (MO) for the improvement of resistance artery relaxation is a potential strategy for the prevention and treatment of hypertension. Aims and Objective: The present study was designed to evaluate the protective effect of MO hydro-ethanol extract on NG-nitro-L-arginine-methyl ester (L-NAME)-induced hypertension and the toxicity profile in Wistar rats and shrimp larvae. Materials and Methods: An experimental hypertensive model was established by administration of L-NAME at 40 mg/kg body weight (BW) by oral gavages to male Wistar rats for 2 weeks and treated with hydro-ethanol extract of MO leaves and losartan. The control group received distilled water. L-NAME group was treated with L-NAME and distilled water. L-NAME-Losartan group was treated with L-NAME and losartan at 100 mg/kg BW. L-NAME-MO group was treated with L-NAME and the hydro- ethanol extract of MO leaves at 500 mg/kg BW. Blood pressure (BP) was measured by tail cuff method. In vitro toxicity study of the extract was performed on Artemia salina larvae using a biological test for the determination of shrimp lethality. A 14 days acute oral toxicity study was evaluated in female rats on a single dose of 2000 mg/kg BW of hydro-ethanol extract of MO. Results: L-NAME treated rats developed significantly increased BP from 110.20 ± 4.46 mmHg to 159.60 ± 4.38 mmHg. Concurrent oral treatment with hydro-ethanol extract of MO leaves decreased the high BP from 159.60 ± 4.38 mmHg to 102.40 ± 5.07 mmHg. No harm was observed at the tested doses in vitro and in vivo toxicity studies. Conclusion: These findings suggest that MO leaves may be potentially useful as a natural product against hypertension.
Keywords: Moringa oleifera; Hypertension; NG-Nitro-L-Arginine-Methyl Ester; Wistar Rat; Toxicity